Researching the Romanian Theatre Archives: A look at the Past from a Contemporary Standpoint - Modreanu, Cristina (Symbolon, 2021)
The archival research has been historically delayed in Romania which means contemporary researchers have a greater responsibility compared to their peers in other countries to recuperate relevant facts from the past. A consistent body of literature regards archives as structures of power, but they are also meant to be looked at with a personal investment, as books by Jaimie Baron and Arlette Farge argue. Based on their arguments as well as on my personal research experience, I am laying the ground in this article for a proactive attitude meant to bring archival research in the frontline of theatre studies in Romania. I chose the “how to” format, with questions and answers for this article, in order to encourage readers to undertake their own research as this is the most appropriate way to draw theoretical conclusions about this process and compare them to the ones already acknowledged in this field.